حضور النص الشعري في الرواية الجزائرية -أحلام مستغانمي وعزالدين جلاوجي أنموذجا- (El-Wahat Journal for Research and Studies, 2025)
Because Of Its Openness To Various Sources˒ The Novel Was Able To Reserve A High Position In The Field Of Creativity And Literary Authorship. We Find That Most Arab Writers Tend To Write The Novel˒ Which Is The Literary Genre Closest To Simulating Reality˒ Of The Texts˒ In Which The Author Was Keen To Give His Text A New Breath Away From The Traditional Stereotype In The Narration Of Events To Embark On A Journey Of Mixing Between The Arts˒ And Specially Poetry˒ In Contemporary Algerian Novel We Find Several Examples Of This Combination. In This Article˒ We Will Discuss The Presence Of The Poetic Text In The Contemporary Algerian Novel - Ahlem Mostaghanemi And Azzeddine Djelaoudji As A Model- And We Will Focus On The Most Prominent Points That Contributed To The Construction Of Fictional Texts Artistically And Aesthetically By Evoking The Element Of Poetry In The Text Of The Novel And The Resulting Artistic Impact.Key Words: Experimentation , Interaction , Novel , Poety , Arts.